Structures of native SV2A reveal the binding mode for tetanus neurotoxin and anti-epileptic racetams - Stephan Schenck; Toon Laeremans; Jan Steyaert; Janine D. Brunner (Nature Communications)
Abstract The synaptic vesicle glycoprotein 2A (SV2A) is a synaptic vesicle (SV) resident with homology to the major facilitator superfamily (MFS) and essential in vertebrate neurotransmission. Despite its unclear physiological role, SV2A is of high medical relevance as it is the target of the anti-epileptic drug Levetiracetam (LEV) and a receptor for clostridial neurotoxins (CNTs), among them presumably tetanus neurotoxin (TeNT). To obtain detailed insights about these molecular interactions we subjected native SV2A, purified from brain tissue, to cryo-EM. We discover that TeNT binds SV2A strikingly different from botulinum neurotoxin A and unveil the precise geometry of TeNT binding to dipartite SV2-ganglioside receptors. The structures deliver compelling support for SV2A as the protein receptor for TeNT in central neurons and reinforce the concepts of the dual receptor hypothesis for CNT entry into neurons. Further, our LEV-bound structure of SV2A reveals the drug-interacting residues, delineates a putative substrate pocket in SV2A and provides insights into the SV2-isoform-specificity of LEV. Our work has implications for CNT engineering from a hitherto unrecognized SV2 binding interface and for improved designs of anti-convulsant drugs in epilepsy treatment.